Novel Mutation in the CHRDL1 Gene Detected in Patients With Megalocornea. Issue 8 (August 2015) - Mangialavori, Domenica; Colao, Emma; Carnevali, Adriano; Bruzzichessi, Donatella; Grillone, Teresa; Perrotti, Nicola; Iuliano, Rodolfo; Scorcia, Vincenzo
Abstract : Purpose: The aim of this study was to determine the mutation associated with X-linked megalocornea (MGC1) found in 2 patients from the same area in southern Italy. Methods: Diagnosis of megalocornea was confirmed by detailed ophthalmic examination in 2 probands from independent families and in another 3 affected family members. Genomic DNA of the probands was used to amplify and sequence all the coding regions of CHRDL1. Results: Megalocornea diagnosis was associated with a novel mutation found in the probands and affected kindreds (5 subjects). The mutation is an 11-base pair deletion that leads to a stop codon in the second coding exon of the CHRDL1 gene. Research on the CHRDL1 mutation was also performed on other family members (11 subjects) not affected by MGC1, and the mutation was not detected in unaffected male family members. Conclusions: The detection of mutations in the CHRDL1 gene is useful for differential diagnosis with different forms of megalocornea.